Secondary Microplastics Generation in the Sea Swash Zone With Coarse Bottom Sediments: Laboratory Experiments - Efimova, Irina; Bagaeva, Margarita; Bagaev, Andrei; Kileso, Alexander; Chubarenko, Irina P. (Frontiers in Marine Science, 2018)
Marine beaches worldwide are nowadays exposed to significant contamination by plastics. On the Baltic beaches, polyethylene, polypropylene, and polystyrene are most abundant. We investigate the generation of microplastics particles (MPs, characteristic size from 0.5 to 5 mm) from larger plastic items in the sea swash zone using a laboratory rotating mixer filled with water and natural coarse beach sediment (marine pebbles). Inclination of the axis of rotation and the volume of the material were adjusted in such a way that mixing resembled a breaking wave in the swash zone. Plastic samples used were of the types most commonly found on the sea beaches. Experimental 2 × 2 cm-large plastic items made of low-density polyethylene (LDPE) were manufactured from common new garbage bags (thickness 5 μm); those made of polypropylene (PP) and polystyrene (PS) were produced from single-use tableware; samples of foamed plastics were presented by cubes (with 2-cm sides) cut out of standard building insulator sheets (foamed PS). Four sets of 24-h-long experiments were conducted (for each type of plastic separately), with step-wise (every 3 h) examination of the generated MPs mass, number of particles, and their qualitative characteristics such as shape, quality of the surface, general behavior while mixing, etc. Statistically significant dependencies are obtained for the increase in mass and in number of MPs with time for all four used kinds of plastics. Brittle solid PS is shown to be the most productive in terms of both mass and number of MPs generated. Anisotropic springing PP is the most resistant. Tensile tearing of LDPE and fragmentation of foamed PS to compounding bubbles/spherules show the variety of mechanisms involved in fragmentation of plastics in the swash zone. Increase in MPs mass and the number of MPs particles with time, as well the link between them, are important for field monitoring and numerical modeling. Potentially shape-selective operation of sieves during sampling and sorting of MPs particles of various shapes is discussed.